(untitled) (European Journal of Education and Psychology, 2018)
School refusal behavior refers to the avoidance of a child attending school and/or persistent difficulty staying in the classroom throughout the school day. Based on a review of the scientific literature, the aim of this study is to describe the current state of research on school refusal, differentiating between the findings and progress made in Spain from those achieved in the international field. For this purpose, the significance of this phenomenon, in addition to associated risk factors and variables, will be reviewed in the child and youth population. In turn, the commonly used assessment methods and most recommended treatment proposals, mainly based on cognitive behavioral therapy, are discussed. The results reveal several gaps and subjects for debate in some areas of knowledge about school refusal behavior, with differences being found between Spanish and international studies. In conclusion, future studies and challenges in this field are required.